PENINGKATAN PRESTASI BELAJAR MATEMATIKA MELALUI PEMBELAJARAN TERPADU MODEL CONNECTED PADA POKOK BAHASAN GARIS DAN SUDUT PADA SISWA KELAS VII E SMP NEGERI 2 DELANGGU KABUPATEN KLATEN SEMESTER II TAHUN PELAJARAN 2011/2012 - ., Gunarto (MAGISTRA, 2012)
Increasing Achievement of Studying Mathematic by Fused Learning Teaching Connected Model at the Topic Line and Angle Class VII E Students of SMP Negeri 2 Delanggu Klaten 2nd Semester at the Year of Learning Teaching 2011/2012 This research aimed to know whether the studying of mathematic by fused learning teaching connected model at the topic line and angle can increase the activities and the students achievement in learning teaching. This research is useful for improving the learning teaching process in class VII E so that the studentsâ achievement in that class increasing. The data analysis of this research used qualitative data and presented at the qualitative distribution. This research is a classroom action research with studying the learning teaching by fused connected model that divided into 3 cyclus. Cyclus I is made 2 times meeting, cyclus II made by 3 times meeting and cyclus III made of 3 times meeting. So, this research done 8 times meeting with twelve time class meeting. Every cyclus made by the planning, acting, observing, evaluating, and reflecting. Collecting data at this research is students checking activities sheet, and cyclus of evaluation test. The result of the research which done with studying mathematic by fused learning teaching connected model at the topic line and angle actually can increase students activities in studying and for students activities cyclus I, II, and III are 43,20%; 56,80%, 68,56% and increasing the students achievements. Cyclus I gets the average mark 58,72% with the percentage achievement 48%. Cyclus II gets the average mark 74,28 with the percentage achievement 72%, and cyclus III gets the average mark 77,6 with the percentage achievement 76%. The conclusion result is that learning teaching connected model can increase the students achievements at the topic line and angle class VII E SMP Negeri 2 Delanggu at the year of learning teaching 2011/2012. Keywords: Fused learning teaching, connected and classroom action research